2000
DOI: 10.1001/jama.283.22.2968
|View full text |Cite
|
Sign up to set email alerts
|

Spread of <EMPH TYPE="ITAL">Mycobacterium tuberculosis</EMPH> in a Community Implementing Recommended Elements of Tuberculosis Control

Abstract: Our results indicate that in a community that has implemented the essential elements of TB control, TB from ongoing transmission of M tuberculosis will continue to develop unless patients are diagnosed earlier and contacts are more completely identified. JAMA. 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 22 publications
4
43
0
2
Order By: Relevance
“…A few researchers [6][7][8] have described how individual TB programs established CI processes as part of their TB control strategy in their communities. One study 9 demonstrated that many contacts were not being identified in a timely manner during the CI process. In another research effort 10 focusing on patient and staff perceptions of the CI, results confirmed the widespread existence of communication difficulties and demonstrated the need for additional staff training.…”
Section: Introductionmentioning
confidence: 99%
“…A few researchers [6][7][8] have described how individual TB programs established CI processes as part of their TB control strategy in their communities. One study 9 demonstrated that many contacts were not being identified in a timely manner during the CI process. In another research effort 10 focusing on patient and staff perceptions of the CI, results confirmed the widespread existence of communication difficulties and demonstrated the need for additional staff training.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, recently transmitted TB is defined as disease occurring within 2 years of infection (1,8,9,31), although some studies have limited the latency period to 1 year (6,15,21) or extended it to 5 years after infection (36). There is a need to decide on the latency period of recent disease development so that outcomes, such as program performances, can be compared.…”
Section: Discussionmentioning
confidence: 99%
“…In San Francisco, for example, the rates of clustered tuberculosis cases decreased significantly both overall and among persons in high-risk groups after a period during which tuberculosis control measures were intensified (66). These studies demonstrate that molecular epidemiology studies can be used as a tool to access and monitor the performance of tuberculosis control programs by targeting interventions in groups at risk that disproportionately contribute to transmission (67). However, to date there are still limits to the widespread use of genotyping to guide tuberculosis control.…”
Section: Transmission and Tuberculosis Controlmentioning
confidence: 90%